2018
DOI: 10.1038/s41598-018-24364-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concentrated Growth Factor (CGF) on the Promotion of Osteogenesis in Bone Marrow Stromal Cells (BMSC) in vivo

Abstract: The therapeutic method traditionally used in bone defect reconstruction is autologous bone grafting. The most common problems affecting this type of repair approach are bone absorption and donor trauma. The approach taken in this study overcomes these problems. Bone marrow stromal cells (BMSCs) provided the crucial seed cells. Fibrin biological scaffolds were formed by combining the BMSCs with concentrated growth factor (CGF). BMSCs were isolated from Wistar rat femurs; CGF was prepared from rat heart blood. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 26 publications
2
54
0
Order By: Relevance
“…Due to the advanced extraction technology and specialized equipment (Medifuge, Silfradent Srl, Italy), the preparation process is simple and does not require any synthetic or catalytic substances. In the present study, the SEM results showed that CGF has a complex porous three-dimensional brin structure, which is consistent with others' results [14,32,33]. This dense brin network can provide a matrix for cell adherence and migration [33,34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Due to the advanced extraction technology and specialized equipment (Medifuge, Silfradent Srl, Italy), the preparation process is simple and does not require any synthetic or catalytic substances. In the present study, the SEM results showed that CGF has a complex porous three-dimensional brin structure, which is consistent with others' results [14,32,33]. This dense brin network can provide a matrix for cell adherence and migration [33,34].…”
Section: Discussionsupporting
confidence: 93%
“…It appears to have more abundant growth factors and a more rigid brin structure than PRP and PRF, due to the special centrifugation process [10,11]. A number of previous studies have demonstrated that CGF's potentials to promote bone formation, tissue repair and regeneration [6,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Honda et al, concentrations of 1–10% of CGF extract had a positive effect on proliferation and differentiation in a dose‐dependent manner, while high concentration (20%) had an inhibitory effect (Honda et al, ). Chen et al, by studying the effect of 5, 10, 20, and 40% CGF, demonstrated more proliferation and differentiation in 10% CGF (Chen et al, ). No dose‐dependent effect was also stated by Hong et al in investigation of the effect of three different concentration of CGF–CCM (1, ½, ¼) (Hong et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As seen in the result of this review, CGF was used alone in in vitro studies, but in in vivo studies, the combination of CGF with stem cells or biomaterials has been reported (Chen et al, ; Durmuslar et al, ; Masuki et al, ; Qiao et al, ; Qiao & An, ; Rodella et al, ). Tissue engineering is a complex of stem cells, scaffold, and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…A part of BMSCs were collected at passage 2 and cryopreservation. Another part was cultured until passage 3, and the BMSCs (passage 3) and its culture supernatant were collected used for the following experiments [22].…”
Section: Isolation and Culture Of Rat Bone Marrow-derived Mesenchymalmentioning
confidence: 99%